Software reuse : bridging with social-awareness : 15th International Conference, ICSR 2016, Limassol, Cyprus, June 5-7, 2016, Proceedings /: bridging with social-awareness : 15th International Conference, ICSR 2016, Limassol, Cyprus, June 5-7, 2016, Proceedings. (2016) - Unknown
No abstract available